Farmers’ rice knowledge and adoption of new cultivars in the Tillabéry region of western Niger - Sow, M.; Seck, P.A.; Maig, I.M.; Laing, M.; Ortíz, R.; Ndjiondjop, M.N. (Springer, 2015)
Tillabéry is the main rice growing region of Niger, and it includes both irrigated and lowland rice. Rice production has stagnated due to several factors this research investigated through farmers’ eyes. Semi-structured group discussions were carried out in 14 villages in which 153 farmers, after giving their informed consent, were individually subjected to a questionnaire, and farmers’ fields and storage facilities were visited. Fields were larger in private irrigation and lowland agrosystems compared to those in public irrigation schemes. The local farmers’ union was the only formal seed dissemination system. Farmers exchanged seed as well as did re-seeding of leftovers from the previous harvest. They indicated Rice yellow mottle virus (RYMV) and bacterial leaf blight (BLB) as the most prevalent biotic stresses in the irrigated agrosystems, but the RYMV-susceptible cultivars IR1529 and ‘Waihidjo’ are still the most popular varieties. Floods, birds, and hippopotamuses were the most damaging agents in lowland agrosystems where the landrace ‘Degaulle’/D5237 was the preferred cultivar. Rice farmers in the region of Tillabéry were aware of the RYMV, could provide good descriptions of its symptoms, but could not establish the real causes of the disease nor its relationship with insects’ prevalence and other cultural practices. However, traditional management strategies were implemented to reduce RYMV epidemics. This situation showed that farmers in the region of Tillabéry were willing to face RYMV epidemic outbreaks while growing their preferred rice cultivars. Good seed availability and absence of seed policy at the time of this study were also detected as bottlenecks in rice production increase in Tillabéry.